ANALISIS TINDAK PIDANA MARITAL RAPE (KEKERASAN SEKSUAL TERHADAP ISTRI) MENURUT HUKUM POSITIF DAN HUKUM PIDANA ISLAM (STUDI KOMPARATIF KASUS PUTUSAN PERKARA NO. 150/ Pid.Sus/ 2017/ PN. Bkl) - karin lisouma adji; karin lisouma adji (Universitas Darussalam Gontor, 2021)
Abstract: A harmonious household is the hope for every husband and wife couple. However, domestic violence is now the main cause of the collapse of the harmony that has been built in a family, due to family problems or economic conditions that trigger domestic violence. The purpose of this research is to find out how judges consider the criminal case of marital rape (sexual violence against wives) and to find out how the legal analysis of this crime is in Islamic criminal law. This research is a library research (Library Research), by collecting data from written sources from books, journals, or magazines that match the title, and also from the Supreme Court Directory website regarding the verdict on the crime of Marital Rape. The results of this study state that the judge's verdict in cases with case numbers. 150 / Pid.Sus / 2017 / PN. Bkl is not in accordance with the Law that regulates this matter, because basically if there is no reason for the wife's forgiveness for the husband's actions, there will be no leniency or reduction of the sentence to 1 year in prison. And the sentence imposed by the judge in this case, if analyzed with a review of Islamic criminal law, is Qishas or it can be completely replaced with a diyat if it is forgiven by the victim or the victim's guardian. As for the diyat that will be dropped for people who have injured the head to the brain, and injured the body to the stomach, by paying the diyat one-third of the mukhaffafah diyat. Then if the diyat cannot be paid with a camel, it must be paid for the camel's price. Some ulama 'said that it was permissible to pay 12,000 dirhams (about 37.44 kg of silver) or with a measure of Rp. 11,861.00, the diyat that the defendant had to pay was Rp. 42.524. 573,00.Keywords: Judge's Consideration, Marital Rape, Law, Excuses